Natural, vaccine-induced immunity and the probability of experiencing SARS-CoV-2 infection in a household cohort in Rio de Janeiro - Michele F. B. da Silva; Lusiele Guaraldo; Leonardo Soares Bastos; Heloisa F. P. Santos; Otávio M. Espíndola; Paola Cristina Resende; Stephanie L. S. Penetra; Anielle Pina-Costa; Isabella C. V. de Moraes; Guilherme A. Calvet; Trevon L. Fuller; Marilda M. Siqueira; et al. (Scientific Reports)
Abstract The impact of COVID-19 vaccines on real-world transmission remains poorly understood and represents a key public health challenge. This study aimed to investigate natural, vaccine-induced immunity and the probability of experiencing SARS-CoV-2 infection in a cohort of families living in Rio de Janeiro. The participants were categorized into immune groups based on recent infection (within the past 9 months) and vaccination status, considering the type of vaccine received, the number of doses, and the strength of their immune response over time. We estimated the transmission probability within clusters using a multivariate model. From May 2020 to June 2023, we enrolled 669 individuals from 182 households; 272 clusters and 288 index cases were identified. Household transmission occurred in 124 (45.6%) clusters. During the pre-VoC period we did not find any factors associated with transmission. In the Gamma/Delta period, previous infections reduced the probability of transmission (OR = 0.088; 95%CI 0.023–0.341), while in the Omicron period, having a healthcare worker in the household (OR = 0.486; 95%CI 0.256–0.921) and hybrid immunity (OR = 0.095; 95%CI 0.010–0.924) decreased the probability of transmission. Our findings provide strong support for the protective effect of regular vaccination against household transmission in a cohort of families exposed to successive SARS-CoV-2 variants.